2012
DOI: 10.1620/tjem.226.11
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nitrogen Compounds in Drinking Water with Incidence of Esophageal Squamous Cell Carcinoma in Shexian, China

Abstract: The incidence of esophageal squamous cell carcinoma (ESCC), which is the eighth most common malignancy worldwide, is highest in China. The purpose of this study was to investigate the association between nitrogen compounds in drinking water with the incidence of ESCC by geographical spatial analysis. The incidence of ESCC is high in Shexian county, China, and environmental factors, particularly nitrogen-contaminated drinking water, are the main suspected risk factors. This study focuses on three nitrogen compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…It is highly likely that nitrosamine and its precursors are very strong risk factors. 39 Although evidence from ecologic studies suggests a correlation between nitrosamine precursors and ESCC incidence, 40 , 41 very few studies have measured nitrosamine and its precursors and evaluated their associations with esophageal cancer risk. The main challenge for such studies is correctly determining exposure to nitrosamine from various sources, including exogenous exposure and endogenous formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is highly likely that nitrosamine and its precursors are very strong risk factors. 39 Although evidence from ecologic studies suggests a correlation between nitrosamine precursors and ESCC incidence, 40 , 41 very few studies have measured nitrosamine and its precursors and evaluated their associations with esophageal cancer risk. The main challenge for such studies is correctly determining exposure to nitrosamine from various sources, including exogenous exposure and endogenous formation.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies found high concentrations of nitrates and nitrites, the precursors of nitrosamine, in drinking water samples, and nitrosamine in food samples. 39 Two ecologic studies, 1 conducted in Cixian 40 and the other in Shexian, 41 found that high concentrations of nitrate nitrogen in well water correlated with ESCC incidence. These findings highlighted the possible role of high levels of nitrate exposure in the pathogenesis of ESCC in high-risk areas.…”
Section: Factors Associated With Esccmentioning
confidence: 99%
“…The previous studies (Wang et al, 2007;Zhang et al, 2012;Dar et al, 2013;Hakami et al, 2013) have suggested that living in rural area is a risk factor for ESCC, as there are worse socioeconomic level, and more unhealthy eating habits. However, the exact statistical difference in prevalence of ESCC between urban and rural areas are not mentioned in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that tobacco smoking, excessive alcohol consumption, and eating pickled vegetables are associated with increased risk of ESCC; these habits can lead to the endogenous generation of nitrosamines, a common type of carcinogen 5 . Furthermore, high concentrations of nitrate nitrogen, the precursor of nitrosamine, in drinking water can increase the risk of ESCC 6 . In contrast, the consumption of fruits and vegetables has been shown to be associated with a reduced risk of ESCC 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%